2012
DOI: 10.1371/journal.pone.0030694
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Gene and Gene-Environmental Interactions of Childhood Asthma: A Multifactor Dimension Reduction Approach

Abstract: BackgroundThe importance of gene-gene and gene-environment interactions on asthma is well documented in literature, but a systematic analysis on the interaction between various genetic and environmental factors is still lacking.Methodology/Principal FindingsWe conducted a population-based, case-control study comprised of seventh-grade children from 14 Taiwanese communities. A total of 235 asthmatic cases and 1,310 non-asthmatic controls were selected for DNA collection and genotyping. We examined the gene-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 60 publications
3
40
0
1
Order By: Relevance
“…The strongest association was between SNPs in IL9 and IL4R (P-value<0.0001). Our results are consistent with previous studies which identified gene-gene interactions as a major component in the pathogenesis of asthma [18]. These results can be explained by the fact that these interleukins share many signaling pathways and some can cross activate others' receptors [19].…”
Section: Discussionsupporting
confidence: 93%
“…The strongest association was between SNPs in IL9 and IL4R (P-value<0.0001). Our results are consistent with previous studies which identified gene-gene interactions as a major component in the pathogenesis of asthma [18]. These results can be explained by the fact that these interleukins share many signaling pathways and some can cross activate others' receptors [19].…”
Section: Discussionsupporting
confidence: 93%
“…It is optimal to combine several analytical methods to detect epistasis effects [35,36]. Because gene-gene interactions may occur through different pathophysiological pathways [36,37], we examined gene-gene interactions for each SNP pair of the three genes. The data showed multiple tendencies toward interactions in the above genes.…”
Section: Discussionmentioning
confidence: 99%
“…In such studies, genotyping is done in a case-control format, which tells about the risk or minor genotype (found more in cases) or protective or major genotype (found more in controls) of a gene. SPSS 49,50 (IBM Corporation, Armonk, NY, USA) and MDR (Vanderbilt University Medical School, Nashville, TN, USA) 51,52 are two well-known software programs that can be used to study such interactions. The input file format depends on the software being used.…”
Section: Gene-environment Interactionmentioning
confidence: 99%